Textile dyeing in Medieval Sudan evidenced by HPLC-MS analyses: Material traces of a disappeared activity. (August 2021) - Wozniak, Magdalena M.; Witkowski, Bartlomiej; Ganeczko, Monika; Gierczak, Tomasz; Biesaga, Magdalena
Highlights: Optical analyses show thread dyeing was a common process. HPLC-MS identified madder, woad ( Isatis tinctoria ), weld and henna as the main dyestuffs used in locally produced textiles. Indigofera tinctoria was positively identified in locally produced textiles from 4th Cataract area. Lac-dye appears mostly in imported textiles, it was probably not used by Nubian dye-masters before the 13th c. Abstract: Numerous textiles dating back to Late Antiquity and Middle Ages found on archaeological sites in the Sudan preserve intact threads with vivid shades of blue, red and yellow. While some of these fabrics were imported, others are products of local textile craft. These textiles are the only witnesses to date of the dyeing activity practiced by the inhabitants of the Nubian kingdoms. The most popular decorative patterns were coloured bands and/or stripes, declined on a plain ground. More sophisticated fabrics preserve traces of geometrical or vegetal ornaments woven in tapestry or in broché. Independently of the technique chosen to embellish the fabric, the weaver needed dyed threads. Those can be coloured before spinning – as raw fibre, or after spinning – as yarns. A closer observation of the threads shows they are usually well dyed on their surface while the core appears less penetrated by the colour, which points to the application of the dye on spun threads. Except for the textiles, there is no other archaeological attestation of dyeing activity to date. The examination of 59 samples by HPLC-MS lead to the identification of the various plant dyes used in Ancient and Medieval Sudan and showed the combinations of these dyes to obtain various tones of a shade and create additional colours such as orange, pink or green.